Influences of family travel motivation and familial needs on destination image and their impact on tourist satisfaction - Osman, Fatin Norain (2016)
The purpose of this study was to investigate the relationship of travel motivation and familial needs towards destination image and its effect on tourists’ satisfaction with tourist behaviour as a moderator. This research intends to scrutinize the importance of travel motivation and familial needs in image of Malaysia and satisfy tourist who are travelling within a destination. This study extends the body of knowledge of family tourism as there was emerging tourism market. Expectancy disconfirmation theory and Maslow’s hierarchy of needs were applied in supporting the proposed relationships and a total of six hypotheses was proposed.Quantitative method is used in analysing the data collected through questionnaires.Multistage sampling method was applied in the selection of respondents. There were 384 respondents from eight locations in Peninsular Malaysia participated in the questionnaire survey. Data screening was carried out to eliminate missing values and outliers in the data collected. The reliability and validity tests, descriptive data analysis, cross tabulation, oneway Anova and multiple regression were conducted as well to analyse the data and test the hypotheses in this study. The results of this study showed that four out of six hypotheses were supported and one hypothesis was partially supported. The findings showed that travel motivation has no significant relationships with affective image.Familial needs are found to be significant with destination image and tourists’ satisfaction.On the other hand, the interaction between tourist behaviour (length of stay and travel arrangement) with destination image and tourist’ satisfaction was not significant. There is no moderation effect of travel behaviour towards the relationship between destination image and tourists’ satisfaction. Limitations of the study and directions for future research are suggested in the last chapter.